Analisis del ataque posicional de balonmano playa masculino y femenino mediante coordenadas polares - Morillo Baro, J. P.; Reigal, R. E.; Hernandez-Mendo, A. (Revista Internacional de Ciencias del Deporte, 2015)
This research aims to provide a new perspective on understanding and differentiation of play behavior in the phase of positional attack in the male and female beach handball. 28 high-level games with Hoisan software were analyzed. The observational design used is nomothetic, monitoring and multidimensional. The taxonomic system has been validated methodologically. Data were subjected to analysis of polar coordinates in its genuine version. To carry out these analyzes on seven focal behaviors were chosen mainly for players who complete the attack and how to create it. The results showed differences in mating behavior in the male and female category. Emphasizes that the positional attack in the female category is geared towards areas left defensive end to an open system depends more on the player who takes the role of caretaker double (specialist) in the men's category, where responsibilities are more spread and attack directed toward the right sideline before a closed defense system. The shoot in pirouette has been shown as the main offensive action in both categories.